Development and Evaluation of an iiPCR Assay for Salmonella and Shigella Detection on a Field-Deployable PCR System - Tian Du; Ji-hong Lin; Jun-hua Zhao; Hai-bo Wang; Qiu-hua Mo (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Salmonella and Shigella are often associated with fecal-oral transmission and cause large-scale outbreaks in centralized catering units and, therefore, should be frequently and strictly monitored, especially among food handlers. However, no specific and sensitive on-site detection method is available until now. Methods. In this study, an insulated isothermal PCR assay for the detection of Salmonella and Shigella on a field-deployable PCR system was developed. Specificity, sensitivity, reproducibility, and clinical accuracy of the assay were characterized and evaluated. Results. The insulated isothermal PCR assay could be completed within 58 minutes with minimal pretreatment needed. The assay was specific and with good reproducibility. The limit of detection was 103 CFU/mL and 101 CFU/mL for Salmonella and Shigella, respectively, which was comparable to multiplex real-time PCR. Mock on-site clinical evaluation results showed that the analytical sensitivity and specificity of the insulated isothermal PCR assay were 100% and 96.6%, while the positive predictive value and negative predictive value were 94.1% and 100%, respectively. Conclusion. Based on our results, we believe that the assay developed herein could serve as an alternative method for preliminary screening and provide a valuable platform for the on-site detection of Salmonella and Shigella, especially in resource-limited and developing countries.